A porphyrin-based MOF modified separator for lithium battery and preparation method and application thereof

CN119050602BActive Publication Date: 2026-11-03DONGFENG MOTOR GRP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411036338.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2026-11-03
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Existing lithium battery separators cannot effectively solve the battery capacity decay caused by the dissolution of transition metal ions to the negative electrode deposition and the safety problems caused by the growth of lithium dendrites in lithium metal batteries in high-energy-density battery systems.

Method used

A porphyrin-based MOF-modified membrane is used. By coating the base membrane with a porphyrin-based MOF coating, the ultra-high specific surface area and regular pore structure of the MOF are utilized to physically adsorb and chemically anchor transition metal ions, uniformly distribute lithium ion flux, and suppress lithium dendrite growth.

Benefits of technology

It effectively improves battery safety and cycle life, significantly enhances capacity retention and coulombic efficiency, suppresses lithium dendrite growth, and ensures battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119050602B_ABST
    Figure CN119050602B_ABST
Patent Text Reader

Abstract

The application provides a porphyrin-based MOF modified separator for a lithium battery, a preparation method and application, and belongs to the field of lithium batteries. The porphyrin-based MOF modified separator comprises a base film and a porphyrin-based MOF coating layer, and the porphyrin-based MOF coating layer is arranged on at least one side surface of the base film. By forming the porphyrin-based MOF coating layer on the base film, at the positive electrode end containing a transition metal element, the MOF modified separator anchors the transition metal ion through the combined adsorption of physical and chemical effects, thereby avoiding the deposition of the transition metal ion on the negative electrode and causing the capacity attenuation of the battery. At the negative electrode end, the MOF modified separator homogenizes the lithium ion flux through the uniform pores and Li-N interaction, so that the deposition of lithium metal becomes more uniform, and the growth of lithium dendrites is inhibited. In summary, the porphyrin-based MOF modified separator solves the capacity attenuation of the battery caused by the deposition of the transition metal ion on the negative electrode in the high specific energy battery system, and solves the safety problem caused by the growth of lithium dendrites in the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to a porphyrin-based MOF-modified separator for lithium batteries, its preparation method, and its application. Background Technology

[0002] With the explosive growth in demand for portable electronic devices and new energy vehicles, the development of high-energy-density, high-power-density, and long-cycle-life rechargeable lithium batteries has become an urgent priority. To overcome range anxiety and meet the demand for long driving range, the batteries currently used in high-end electric vehicles primarily use high-nickel ternary materials as the cathode.

[0003] However, the capacity decay caused by the dissolution of transition metal ions to the negative electrode in high-energy-density battery systems, and the safety issues caused by the growth of lithium dendrites in lithium metal batteries, seriously affect the application of lithium batteries. To address these two application problems, in addition to conventional material modification and electrode interface modification, functional coating modification at the separator end is a practical and effective solution. For example, a PVDF-coated separator is disclosed in the prior art, which has characteristics such as low internal resistance, high (thickness / porosity) uniformity, good mechanical properties, and good chemical and electrochemical stability. Due to the presence of the nanofiber coating, this novel separator has better compatibility and adhesion to lithium battery electrodes than ordinary battery separators, and can significantly improve the battery's high-temperature resistance and safety. However, the high crystallinity and hydrophobic surface of the PVDF-coated separator lead to obstructed lithium-ion transport and poor electrolyte retention. Especially for nickel-containing layered material systems and lithium metal systems, it cannot specifically solve the problems of transition metal ion dissolution to the negative electrode and lithium metal deposition. Meanwhile, existing technologies disclose an alumina / boehmite coated separator. Ultrafine alumina possesses excellent conductivity, thermal stability, and corrosion resistance, but suffers from low energy density and high cost. Boehmite, on the other hand, offers high safety, good cycle life, and low self-discharge rate, but exhibits lower conductivity, relatively lower specific capacity, and higher cost. However, for nickel-containing layered material systems and lithium metal systems, the alumina / boehmite coated separator cannot specifically address the issues of transition metal ion dissolution and deposition at the negative electrode, or lithium metal deposition. Therefore, there is an urgent need to address, at the separator level, the battery capacity decay caused by transition metal ion dissolution and deposition at the negative electrode in high-energy-density battery systems, as well as the safety issues arising from lithium dendrite growth in lithium metal batteries. Summary of the Invention

[0004] This application provides a porphyrin-based MOF-modified separator for lithium batteries, its preparation method, and its application, in order to solve the battery capacity decay caused by the dissolution of transition metal ions to the negative electrode in high-energy-density battery systems, as well as the safety problems caused by the growth of lithium dendrites in lithium metal batteries.

[0005] In a first aspect, this application provides a porphyrin-based MOF-modified separator for lithium batteries, wherein the porphyrin-based MOF-modified separator is used in lithium batteries, the positive electrode active material of the lithium batteries contains a transition metal element, and the porphyrin-based MOF-modified separator comprises:

[0006] Base film; and

[0007] A porphyrin-based MOF coating is disposed on at least one side surface of the base film, wherein the coating slurry of the porphyrin-based MOF coating comprises a porphyrin-based MOF material, and the porphyrin-based MOF material comprises one or more of PCN222 and PCN223.

[0008] Optionally, the coating slurry further includes a dispersant, a binder, and a solvent. The mass ratio of the porphyrin-based MOF material, the dispersant, and the binder is (90–96):(0.2–3):(1–10).

[0009] Optionally, the dispersant includes one or more of sodium carboxymethyl cellulose and polyacrylates.

[0010] Optionally, the adhesive includes one or more of polyvinylidene fluoride, polyacrylic acid, and sodium alginate.

[0011] Optionally, the solvent includes one or more of water, N-methylpyrrolidone, ethanol, and acetone.

[0012] Optionally, the base film includes one or more of the following: polyolefin, polyvinylidene fluoride, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyimide, cellulose, and polyurethane.

[0013] Optionally, the thickness of the base film is 9 μm to 11 μm, and the thickness of the porphyrin-based MOF coating is 2 μm to 3 μm.

[0014] Secondly, this application provides a method for preparing the porphyrin-based MOF-modified membrane according to any embodiment of the first aspect, the method comprising:

[0015] Obtain porphyrin-based MOF materials;

[0016] The porphyrin-based MOF material is mixed with a dispersant, a binder, and a solvent to obtain a coating slurry;

[0017] The coating slurry is applied to at least one side of the surface of the base film to obtain a porphyrin-based MOF-modified membrane.

[0018] Optionally, the baking temperature for the coating is 70°C to 90°C.

[0019] Thirdly, this application provides a lithium battery, which includes: a positive electrode, a negative electrode, an electrolyte, and a separator. The active material of the positive electrode includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, lithium manganese iron phosphate, and lithium nickel manganese oxide. The separator is a porphyrin-based MOF-modified separator as described in any embodiment of the first aspect.

[0020] The technical solutions provided in this application have the following advantages compared with the prior art:

[0021] This application provides a porphyrin-based MOF-modified separator for lithium-ion batteries. The porphyrin-based MOF-modified separator is used in lithium-ion batteries where the positive electrode active material contains a transition metal element. The porphyrin-based MOF-modified separator includes a base film and a porphyrin-based MOF coating. The porphyrin-based MOF coating is coated on at least one surface of the base film. The coating slurry of the porphyrin-based MOF coating includes a porphyrin-based MOF material, specifically one or more of PCN222 and PCN223. By forming a porphyrin-based MOF coating on the base film, the porphyrin-based MOF possesses an ultra-high specific surface area and a regular pore structure, while its pores contain abundant and uniform nitrogen-containing active sites. On the one hand, at the positive electrode, it can physically adsorb transition metal ions dissolved from the metal oxide positive electrode using the capillary action of its pores. Furthermore, the active nitrogen nodes within its pores can coordinate with the transition metal ions, anchoring them through a combination of physical and chemical adsorption. This modified separator then blocks the transition metal ions at the positive electrode, preventing their deposition at the negative electrode and thus avoiding capacity decay. On the other hand, at the negative electrode, especially the lithium metal negative electrode, this MOF-modified separator can homogenize the lithium ion flux through its uniform pores and Li-N interactions, resulting in more uniform lithium metal deposition and suppressing lithium dendrite growth, effectively ensuring battery safety. This solves the battery capacity decay caused by the dissolution of transition metal ions to the negative electrode in high-energy-density battery systems, as well as the safety issues caused by lithium dendrite growth in lithium metal batteries. Attached Figure Description

[0022] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0023] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1This is a schematic flowchart illustrating a method for preparing a porphyrin-based MOF-modified separator for lithium batteries, as provided in an embodiment of this application. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0026] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0027] Furthermore, in the description of this application, the terms "comprising," "including," etc., mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.

[0028] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0029] The inventive concept of this application is:

[0030] To overcome range anxiety and meet the demand for long driving range, the batteries currently used in high-end electric vehicles primarily use high-nickel ternary materials as the cathode. While increasing the nickel content significantly improves the energy density of lithium batteries, it also leads to a marked decrease in thermal stability and poorer cycle performance. Furthermore, with increasing nickel content (especially in high-nickel ternary batteries with nickel content >60%), the sintering temperature decreases, resulting in reduced lithium salt volatilization and increased lithium salt residue on the material surface, forming lithium oxide (Li2O). This oxide readily adsorbs CO2 and H2O from the air, forming Li2CO3 and LiOH on the material surface. Li2CO3 decomposes during high-temperature, fully charged, high-potential storage, producing gas. LiOH reacts with the lithium salt in the electrolyte to generate HF. HF etches the cathode material, causing transition metals to dissolve and deposit through the separator on the anode, a major cause of battery capacity decay. Simultaneously, the deposited metal foreign matter may puncture the separator, threatening battery safety.

[0031] Meanwhile, in industrial pre-research projects, lithium metal batteries using metallic lithium as the negative electrode have attracted much attention in order to further improve the energy density of batteries. They possess ultra-high theoretical specific capacity (3860 mAh / g), extremely low standard redox potential (-3.04 V), and extremely low density, demonstrating excellent performance in solid-state batteries and novel battery systems such as lithium-sulfur batteries / lithium-air batteries. However, the development of lithium metal batteries also faces many challenges. The most critical is that the unevenness of lithium flux and electrode exchange current density can lead to the growth of lithium dendrites. The continuous growth of lithium dendrites can puncture the separator, causing safety issues.

[0032] For the two application scenarios mentioned above, in addition to conventional material modification and electrode interface modification, functional coating modification from the diaphragm end is a practical and effective solution.

[0033] Therefore, to address the battery capacity decay caused by the dissolution of transition metal ions to the negative electrode in high-energy-density battery systems, and the safety issues posed by the growth of lithium dendrites in lithium metal batteries, this application provides a porphyrin-based metal-organic framework (MOF) modified separator. This porphyrin-based MOF possesses an ultra-high specific surface area and a regular pore structure, while its pores contain abundant and uniform nitrogen-containing active sites. On the one hand, at the positive electrode, it can physically adsorb transition metal ions dissolved from the metal oxide positive electrode using the capillary action of the pores, and the active nitrogen nodes within its pores can coordinate with the transition metal ions, anchoring them through a combination of physical and chemical adsorption. The modified separator then blocks these transition metal ions at the positive electrode, preventing their deposition at the negative electrode and thus avoiding battery capacity decay. On the other hand, at the negative electrode, especially the lithium metal negative electrode, this MOF modified separator can homogenize the lithium ion flux through its uniform pores and Li-N interactions, making lithium metal deposition more uniform, suppressing the growth of lithium dendrites, and effectively ensuring battery safety.

[0034] This application provides a porphyrin-based MOF-modified separator for lithium batteries. The porphyrin-based MOF-modified separator is used in lithium batteries, and the positive electrode active material of the lithium battery contains a transition metal element. The porphyrin-based MOF-modified separator includes: a base film; and a porphyrin-based MOF coating. The porphyrin-based MOF coating is disposed on at least one side surface of the base film. The coating slurry of the porphyrin-based MOF coating includes a porphyrin-based MOF material, and the porphyrin-based MOF material includes one or more of PCN222 and PCN223.

[0035] Through extensive research, this application selects specific types of porphyrin-based MOF materials (PCN222 and PCN223) to modify the separator. These porphyrin-based MOFs possess ultra-high specific surface area and regular pore structure. At the same time, their pores contain abundant and uniform nitrogen-containing active sites, which can not only adsorb and anchor transition metal ions dissolved from the cathode, but also utilize the uniform pores and Li-N interactions to homogenize lithium ion flux, suppress lithium dendrite growth, and effectively improve battery safety performance and cycle life.

[0036] In some embodiments, the coating slurry further includes a dispersant, a binder, and a solvent. The mass ratio of the porphyrin-based MOF material, the dispersant, and the binder is (90–96):(0.2–3):(1–10).

[0037] In the above embodiments, controlling the mass ratio of porphyrin-based MOF material, dispersant, and binder to porphyrin-based MOF material: dispersant: binder = (90-96):(0.2-3):(1-10) has the following positive effects: By adding the dispersant, the affinity between the particle surface of the porphyrin-based MOF material and the medium can be improved, allowing the porphyrin-based MOF material particles to achieve a state of easy wetting and uniform dispersion in the coating slurry, thereby preventing the agglomeration of the porphyrin-based MOF material particles; while the binder ensures that the porphyrin-based MOF material particles adhere tightly to the base film. The rational design of the coating slurry composition in this application ensures that the porphyrin-based MOF material can be successfully coated onto the surface of the base film to form a coating layer. For example, the mass ratio of porphyrin-based MOF material, dispersant, and binder can be 90:0.2:9.8, 90:1:9, 90:2:8, 90:3:7, 95:0.2:4.8, 95:1:4, 95:2:3, 95:3:2, 96:0.2:3.8, 96:1:3, 96:2:2, 96:3:1, etc.

[0038] In some embodiments, the dispersant includes one or more of sodium carboxymethyl cellulose and polyacrylates.

[0039] In some embodiments, the adhesive includes one or more of polyvinylidene fluoride, polyacrylic acid, and sodium alginate.

[0040] In some embodiments, the solvent includes one or more of water, N-methylpyrrolidone, ethanol, and acetone.

[0041] In some embodiments, the base film comprises one or more of the following: polyolefin, polyvinylidene fluoride, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyimide, cellulose, and polyurethane.

[0042] In some embodiments, the thickness of the base film is 9 μm to 11 μm, and the thickness of the porphyrin-based MOF coating is 2 μm to 3 μm.

[0043] Figure 1 This is a schematic flowchart illustrating a method for preparing a porphyrin-based MOF-modified separator for lithium batteries, as provided in an embodiment of this application.

[0044] Please see Figure 1 This application provides a method for preparing the porphyrin-based MOF-modified membrane according to any one of the above embodiments, the method comprising:

[0045] S1. Obtain porphyrin-based MOF materials;

[0046] In some embodiments, obtaining the porphyrin-based MOF material includes:

[0047] S101. Weigh a certain amount of methyl p-formylbenzoate into a three-necked flask, and add an appropriate amount of propionic acid to dissolve it completely. Set up a reflux condenser, heat to 120°C under an argon atmosphere in the dark, and then slowly add an appropriate amount of pyrrole into the flask under the same conditions. After reacting at 120°C for a short time, raise the temperature to 140°C and react for 12 hours. After the reaction is complete, filter, wash repeatedly with deionized water and ethanol, and dry to obtain the ligand precursor tetrakis(4-carboxymethyl ester phenyl)porphyrin;

[0048] S102. Weigh a certain amount of tetra(4-carboxymethyl ester phenyl)porphyrin into a round-bottom flask, add appropriate amounts of methanol and tetrahydrofuran to dissolve it completely. Weigh appropriate amounts of potassium hydroxide and deionized water to prepare an alkaline solution, add it to the above solution, slowly heat to 85℃, and reflux for 12 hours. After the reaction is complete, rotary evaporate the solution, add deionized water to dissolve it, acidify with acetic acid until the pH of the system is ≥5, filter the resulting suspension, wash with deionized water and dry to obtain the ligand tetra(4-carboxyphenyl)porphyrin;

[0049] S103. Weigh a certain amount of zirconium salt and tetra(4-carboxyphenyl)porphyrin into a glass bottle, add DMF to dissolve it completely, then add an appropriate amount of pH adjuster, and react at 120℃ for 12 h. After the reaction is complete and cooled to room temperature, centrifuge, pour out the supernatant, add an appropriate amount of DMF to disperse it fully, repeat the exchange several times, dry and grind to obtain porphyrin-based MOF.

[0050] In some embodiments, the zirconium salt includes zirconium oxychloride hydrate.

[0051] In some embodiments, the pH adjuster determines the type of porphyrin-based MOF; wherein, when the pH adjuster is p-tert-butylbenzoic acid, the porphyrin-based MOF material is PCN222; and when the pH adjuster is p-chlorobenzoic acid, the porphyrin-based MOF material is PCN223.

[0052] S2. The porphyrin-based MOF material is mixed with a dispersant, a binder, and a solvent to obtain a coating slurry;

[0053] S3. The coating slurry is applied to at least one side of the base film to obtain a porphyrin-based MOF-modified membrane.

[0054] In some embodiments, the baking temperature for the coating is 70°C to 90°C.

[0055] In the above embodiments, controlling the baking temperature of the coating efficiently removes the solvent from the coating slurry and prevents the coating from cracking. For example, the baking temperature of the coating can be 70°C, 75°C, 80°C, 85°C, 90°C, etc.

[0056] The product prepared by the method of preparing the porphyrin-based MOF modified membrane is the aforementioned porphyrin-based MOF modified membrane. The chemical composition and microstructure of the porphyrin-based MOF modified membrane prepared by this method can be referred to the above embodiments. Since the method of preparing the porphyrin-based MOF modified membrane adopts some or all of the technical solutions of the porphyrin-based MOF modified membrane embodiments, it has at least all the beneficial effects brought about by the technical solutions of the porphyrin-based MOF modified membrane embodiments, which will not be elaborated here.

[0057] Based on a general inventive concept, this application provides a lithium battery, which includes: a positive electrode, a negative electrode, an electrolyte, and a separator. The active material of the positive electrode includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, lithium manganese iron phosphate, and lithium nickel manganese oxide. The separator is a porphyrin-based MOF-modified separator as described in any of the above embodiments.

[0058] In some embodiments, the negative electrode includes one or more of graphite negative electrode, silicon-carbon negative electrode, and lithium metal negative electrode; the electrolyte is composed of lithium salt and carbonate solvent.

[0059] The lithium battery provided in this application, when tested at a current density of 1C, retains a capacity of ≥99% after 50 cycles.

[0060] The lithium battery provided in this application has an A / cm² voltage of 1mA / cm². 2 Charge-discharge tests were conducted at current density, with a coulombic efficiency of ≥99.8% in the first week and an average coulombic efficiency of ≥99.6% over 200 weeks.

[0061] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards. If there is no corresponding industry standard, then common international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0062] Example 1

[0063] This embodiment provides a method for preparing a porphyrin-based MOF-modified membrane, the specific steps of which are as follows:

[0064] S11, PCN222 powder is obtained;

[0065] S21. Weigh the raw materials according to the mass ratio of PCN222, CMC and PAA of 95:1:4. Mix CMC and deionized water evenly to obtain a dispersion. Add PCN222 powder material to the dispersion, then add PAA and stir for 30 minutes to obtain a coating slurry.

[0066] S31 uses a microgravure coating machine to coat the slurry on both sides of a PE base film. The base film thickness is 9μm and the coating thickness is 2μm, thus obtaining a porphyrin-based MOF modified diaphragm.

[0067] Example 2

[0068] This embodiment provides a method for preparing a porphyrin-based MOF-modified membrane, the specific steps of which are as follows:

[0069] S11, PCN223 powder is obtained;

[0070] S21. Weigh the raw materials according to the mass ratio of PCN223, CMC and PAA of 95:1:4. Mix CMC and deionized water evenly to obtain a dispersion. Add PCN223 powder material to the dispersion, then add PAA and stir for 30 minutes to obtain a coating slurry.

[0071] S31 uses a microgravure coating machine to coat the slurry on both sides of a PE base film. The base film thickness is 9μm and the coating thickness is 2μm, thus obtaining a porphyrin-based MOF modified diaphragm.

[0072] Example 3

[0073] This embodiment provides a method for preparing a lithium battery, the specific steps of which are as follows:

[0074] Using the coated separator obtained in Example 1 as the separator, commercially available NCM811 as the positive electrode, commercially available graphite as the negative electrode, and a mature commercial electrolyte, a small pouch battery was assembled on an environmentally controlled pouch line.

[0075] Example 4

[0076] This embodiment provides a method for preparing a lithium battery, the specific steps of which are as follows:

[0077] Using the coated separator obtained in Example 2 as the separator, commercially available NCM811 as the positive electrode, commercially available graphite as the negative electrode, and a mature commercial electrolyte, a small pouch battery was assembled on an environmentally controlled pouch line.

[0078] Example 5

[0079] This embodiment provides a method for preparing a lithium battery, the specific steps of which are as follows:

[0080] Using the coated membrane obtained in Example 1 as the membrane, and selecting a mature electrolyte, a Li||Li symmetric cell (CR2032 coin cell) was assembled in an argon-filled glove box.

[0081] Example 6

[0082] This embodiment provides a method for preparing a lithium battery, the specific steps of which are as follows:

[0083] Using the coated membrane obtained in Example 2 as the membrane, and selecting a mature electrolyte, a Li||Li symmetric cell (CR2032 coin cell) was assembled in an argon-filled glove box.

[0084] Comparative Example 1

[0085] This comparative example provides a commercially available PVDF diaphragm.

[0086] Comparative Example 2

[0087] This comparative example provides a method for preparing a lithium battery, the specific steps of which are as follows:

[0088] Using the commercial separator from Comparative Example 1, commercially available NCM811 was used as the positive electrode, commercially available graphite as the negative electrode, and a mature commercially available electrolyte, small pouch batteries were assembled on an environmentally controlled pouch line.

[0089] Comparative Example 3

[0090] This comparative example provides a method for preparing a lithium battery, the specific steps of which are as follows:

[0091] Using the commercially available separator from Comparative Example 1 and a mature electrolyte, Li||Li symmetric cells (CR2032 coin cells) were assembled in an argon-filled glove box.

[0092] Performance test results of the examples and comparative examples:

[0093] The membranes prepared in Examples 1 and 2 and the commercial membrane provided in Comparative Example 1 were placed in NiCl2 aqueous solution for adsorption tests, and the color change of the solution was observed. The results are shown in Table 1.

[0094] Table 1. Adsorption test results of the membrane in NiCl2 aqueous solution.

[0095] Group <![CDATA[Color change of nickel chloride aqueous solution]]> Example 1 From green to colorless Example 2 From green to colorless Comparative Example 1 No change

[0096] The batteries prepared in Examples 3 and 4 were subjected to charge-discharge tests at a current density of 1C. The capacity retention rate after 50 cycles was recorded and compared with that of the battery in Comparative Example 2. The results are shown in Table 2.

[0097] Table 2 shows the charge-discharge test results of the lithium batteries prepared in Examples 3 and 4 and Comparative Example 2.

[0098] Group Capacity retention after 50 cycles Example 3 99.5% Example 4 99.1% Comparative Example 2 97.9%

[0099] As shown in Table 2, the battery assembled using the porphyrin-based MOF-modified composite separator exhibits significantly improved cycle stability compared to ordinary commercial separators.

[0100] The batteries prepared in Examples 5, 6 and Comparative Example 3 were subjected to charge-discharge tests at a current density of 1 mA / cm². 2 The cycle length was 200 cycles, and all lithium metal from the negative electrode was removed on the 201st cycle. The average coulombic efficiency was then calculated. The results are shown in Table 2.

[0101] Table 3 shows the charge-discharge test results of the lithium batteries prepared in Examples 5 and 6 and Comparative Example 3.

[0102]

[0103]

[0104] As shown in Table 3, the average coulombic efficiency of the battery assembled using the porphyrin-modified MOF composite separator is significantly improved compared with that of ordinary commercial separators, indicating that it inhibits the growth of lithium dendrites and reduces the formation of dead lithium.

[0105] Furthermore, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0106] In this embodiment of the invention, a porphyrin-based metal-organic framework (MOF) modified separator is provided. At the positive electrode, it can anchor transition metal ions through a combination of physical and chemical adsorption, blocking them at the positive electrode and preventing their deposition at the negative electrode, thus avoiding battery capacity degradation. At the lithium metal negative electrode, its uniform pores and Li-N interactions homogenize the lithium ion flux, resulting in more uniform lithium metal deposition, suppressing lithium dendrite growth, and effectively ensuring battery safety.

[0107] In this embodiment of the invention, the safety performance and cycle life of the battery are effectively improved by using a porphyrin-based MOF-modified separator. The provided lithium battery, after 50 charge-discharge cycles at a 1C current density, exhibits a capacity retention of ≥99%. (At 1mA / cm...) 2 Charge-discharge tests were conducted at current density, with a coulombic efficiency of ≥99.8% in the first week and an average coulombic efficiency of ≥99.6% over 200 weeks.

[0108] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A porphyrin-based MOF-modified separator for lithium batteries, characterized in that, The porphyrin-based MOF-modified separator is used in lithium batteries, wherein the positive electrode active material of the lithium battery contains a transition metal element, and the porphyrin-based MOF-modified separator comprises: Base film; and A porphyrin-based MOF coating is disposed on at least one side surface of the base film. The coating slurry of the porphyrin-based MOF coating includes a porphyrin-based MOF material, a dispersant, and a binder. The porphyrin-based MOF material includes one or more of PCN222 and PCN223. The mass ratio of the porphyrin-based MOF material, the dispersant, and the binder is (90~96):(0.2~3):(1~10). The thickness of the base film is 9μm~11μm, and the thickness of the porphyrin-based MOF coating is 2μm~3μm.

2. The porphyrin-based MOF-modified membrane according to claim 1, characterized in that, The coating slurry also includes a solvent.

3. The porphyrin-based MOF-modified membrane according to claim 2, characterized in that, The dispersant includes one or more of sodium carboxymethyl cellulose and polyacrylates.

4. The porphyrin-based MOF-modified membrane according to claim 2, characterized in that, The adhesive includes one or more of polyvinylidene fluoride, polyacrylic acid, and sodium alginate.

5. The porphyrin-based MOF-modified membrane according to claim 2, characterized in that, The solvent includes one or more of water, N-methylpyrrolidone, ethanol, and acetone.

6. The porphyrin-based MOF-modified membrane according to claim 2, characterized in that, The base film includes one or more of the following: polyolefin, polyvinylidene fluoride, polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl chloride, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyimide, cellulose, and polyurethane.

7. A method for preparing a porphyrin-based MOF-modified membrane according to any one of claims 1 to 6, characterized in that, The method includes: Obtain porphyrin-based MOF materials; The porphyrin-based MOF material is mixed with a dispersant, a binder, and a solvent to obtain a coating slurry; The coating slurry is applied to at least one side of the surface of the base film to obtain a porphyrin-based MOF-modified membrane.

8. The method according to claim 7, characterized in that, The baking temperature for the coating is 70℃~90℃.

9. A lithium battery, characterized in that, The lithium battery includes: a positive electrode, a negative electrode, an electrolyte, and a separator. The active material of the positive electrode includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, lithium manganese iron phosphate, and lithium nickel manganese oxide. The separator is a porphyrin-based MOF-modified separator as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Modified metal organic framework modified battery diaphragm and preparation method thereof

    CN118249035A